2011
DOI: 10.1007/s12282-011-0275-4
|View full text |Cite
|
Sign up to set email alerts
|

Prospective ultrasonographic prediction of sentinel lymph node metastasis by real-time virtual sonography constructed with three-dimensional computed tomography–lymphography in breast cancer patients

Abstract: If cortical thickness of the SLN is less than 2.5 mm, SLN metastasis is unlikely to be present. If cortical thickness of the SLN is at least 2.5 mm, preoperative fine-needle aspiration cytology may be recommended to verify the possibility of SLN metastasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Recent advances in imaging techniques have led to improved diagnosis of lymphedema. Computed tomography 6 and magnetic resonance imaging 7 with and without lymphography are commonly used for the display of lymphatics; a novel, easy, safe, and cost-effective technique, however, has also been recently elaborated to show lymphatic vasculature without radionuclide tracer using near-infrared fluorescent imaging where the water-soluble indocyanine-green dye is capable of illuminating especially the superficial lymphatic network. 8 Prophylaxis Total or segmental limb volume changes (≥3%) should alert caregivers to the early development of lymphedema.…”
Section: Diagnosismentioning
confidence: 99%
“…Recent advances in imaging techniques have led to improved diagnosis of lymphedema. Computed tomography 6 and magnetic resonance imaging 7 with and without lymphography are commonly used for the display of lymphatics; a novel, easy, safe, and cost-effective technique, however, has also been recently elaborated to show lymphatic vasculature without radionuclide tracer using near-infrared fluorescent imaging where the water-soluble indocyanine-green dye is capable of illuminating especially the superficial lymphatic network. 8 Prophylaxis Total or segmental limb volume changes (≥3%) should alert caregivers to the early development of lymphedema.…”
Section: Diagnosismentioning
confidence: 99%
“…Recently, fusion image with real-time US and computed tomography (CT) has been introduced in interventional radiology [13] [14]. In the chest, fusion image can be used to assist in detecting the pleural-lesion contact area in extremely small solid nodules.…”
Section: Introductionmentioning
confidence: 99%
“…Yamamoto et al (10) reported that fusion imaging of real-time ultrasound and CT-lymphography improved the preoperative detection of sentinel lymph nodes, and its accuracy for predicting metastasis was 81%. Breast MRI and ultrasound are the most popular imaging modalities for the assessment of preoperative stages of breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Breast MRI and ultrasound are the most popular imaging modalities for the assessment of preoperative stages of breast cancer. Breast MRI is a sensitive imaging technique for detection of breast cancer; however, it has a wide range of specificity and high false positive rates (1011121314). Breast ultrasound is a very convenient way to evaluate breast and lymph nodes, but is dependent on the doctors' experience and equipment.…”
Section: Introductionmentioning
confidence: 99%